The Moderation Effect of Boycott Counternarrative on the Effect of Animosity on Purchase Amount - Isjwardhani, Fawzia Rahmah Gieza (Syntax Literate, 2025)
This study aims to empirically test the boycott counternarrative and how it affects the McDonald's boycott case that occurred in Indonesia, especially in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The boycott campaign occurred as a result of the war between Israel and Palestine and is related to America which has diplomatic relations with Israel as the country of origin of McDonald's. This study refers to the theory of planned behavior and analyzes how it is applied in the context of a boycott. This study was conducted on McDonald's consumers spread across Jabodetabek and exposed to information related to the counter-boycott narrative targeted at McDonald's. The study was conducted on 377 respondents and the data obtained will be processed using structured equation modeling. This study is expected to provide an overview of whether the boycott counternarrative has succeeded in weakening the effect of animosity over McDonald's which provides support for the Israeli army on the purchase amount of respondents at McDonald's. Specifically, there have been no studies that empirically study the boycott counternarrative either in the context of McDonald's or in other contexts. The results of data processing using the PLS-SEM method show that boycott counternarrative has an effect on purchase amount by moderating the indirect relationship between animosity and purchase amount. This condition is in accordance with the research hypothesis which states that boycott counternarrative causes an increase in purchase amount from the moderation effect on the interaction of the boycott attitude variable with boycott intention. The moderating effect of boycott counternarrative on the indirect relationship between the animosity variable and purchase amount provides novelty for research that develops the theory of planned behavior.